An analysis of the practices of Muhammad (pbuh) on resolving conflicts (Journal of the Bangladesh Association of Young Researchers, 2011)
Conflict is an inevitable phenomenon of human life as everyone strives for the peace, which can be established only on the absence of conflict. So, naturally, the presence of various conflicts in our life cycle, from the very person to the greater field of international arena, and the process to avoid or resolve these have been taken as a major concern by the social thinkers. In this regard, Muslim scholars also give their thoughtful suggestion on principles and methods of conflict resolution according to the Islamic ideology that basically consists of the Quran and of the tradition of the Prophet (pbuh). In this paper, among these two core sources of Islam, the traditions of Prophet (pbuh) are described to some extent that would be helpful to regulate a new method for conflict management. This paper is also an attempt to make proper evidences from the history for the settlement of disputes of the present world. With the comparison of conventional and Islamic process of conflict resolution it also can help to add suitable dimension in this context.    Key words: Conflict resolution; Dispute; Islam; Peace; Prophet Muhammad (pbuh).DOI: 10.3329/jbayr.v1i1.6840Journal of Bangladesh Association of Young Researchers Vol.1(1) 2011 pp.109-125